Les « nouvelles zones urbaines » de Hanoi (Vietnam) : dynamiques spatiales et enjeux territoriaux - Danielle Labbé; Clément Musil (M@ppemonde)
Faced with increasingly rapid urban sprawl, developing Asian cities struggle to control their urbanization. While Hanoi, the capital of Vietnam, is also struggling to curb its own rapid urbanization, in the 1990s, the government adopted a new policy to orient and shape urban expansion. This policy is based on the planning and construction of “new urban areas” (khu do thi moi). This article provides a cartographic analysis of the implementation of these areas across the city-province’s territory and examines issues related to their territorial expansion.